Web-Based Interventions for Pregnant Women With Gestational Diabetes Mellitus: Systematic Review and Meta-analysis - Pingping Guo; Dandan Chen; Ping Xu; Xiaojuan Wang; Wei Zhang; Minna Mao; Qiong Zheng; Ying Jin; Suwen Feng (JMIR Publications, 2023)
BackgroundEffective management of gestational diabetes mellitus (GDM) is essential because it is one of the most prevalent diseases during pregnancy, and the consequent condition maternal hyperglycemia is closely related to considerable short- and long-term maternal and neonatal complications. Web-based interventions (WBIs), defined as therapeutic interventions offered via the web, have been implemented to assist in managing GDM owing to their advantages of high accessibility and efficiency, but findings across relevant studies are inconsistent. ObjectiveThis systematic review and meta-analysis aimed to evaluate the effectiveness of WBIs on glycemic control among pregnant women with GDM; examine whether specific types of intervention interactivity, format, and technology have beneficial effects on maternal glycemic control; and comprehensively assess the efficacy of WBIs in maternal behavioral outcomes, cognitive and attitudinal outcomes, mental health, maternal and neonatal clinical outcomes, and medical service use and costs among pregnant women with GDM. MethodsPubMed, Embase, Cochrane Library, Web of Science, CINAHL, and PsycINFO were searched from their respective inception to November 19, 2022, to identify relevant randomized controlled trials and controlled clinical trials. The methodological quality of the included studies was assessed using the Effective Public Health Practice Project tool. Where possible, the data for all outcomes were meta-analyzed using the Stata software (version 12.0; StataCorp). Overall, 3 subgroup analyses and post hoc sensitivity analyses of maternal glycemic control parameters were performed. ResultsOverall, 25 publications arising from 21 randomized controlled trials and controlled clinical trials were included. The overall meta-analyses on glycemic control parameters demonstrated that WBIs could significantly improve fasting blood glucose (standardized mean difference=−1.764, 95% CI −2.972 to −0.557; P=.004) and 2-hour postprandial blood glucose (standardized mean difference=−1.433, 95% CI −2.561 to −0.304; P=.01) compared with the control group, whereas no significant effect was found on glycated hemoglobin and 1-hour postprandial blood glucose. The results of the subgroup analyses indicated that mobile app-delivered interventions with a personalized format and interactive function showed more beneficial effects on maternal glycemic control. Moreover, WBIs could significantly enhance compliance with the self-monitoring of blood glucose; increase the rate of normal vaginal delivery; and decrease the chance of emergency cesarean, admission to the neonatal intensive care unit, and composite neonatal complications. GDM knowledge, risk perception of the disease, self-efficacy, satisfaction with care, and medical service use of the participants in the WBI group were also improved compared with the control group. However, the effectiveness of WBIs on other secondary outcomes was either nonsignificant or uncertain. ConclusionsWBIs are a promising approach to GDM management. Personalized, interactive, and mobile app-delivered interventions seem more worthy of being recommended for future clinical practice. Further high-quality studies are required to verify these findings before making broad recommendations. Trial RegistrationPROSPERO CRD42022296625; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=296625